Needs Analysis for Developing an Augmented Reality-Based Picture Storybook Integrating Majalengka’s Local Wisdom to Support Elementary Students’ Creative Thinking Skills - Yati Suratiawati; Aji Septiaji; Devi Afriyuni Yonanda (Journal of General Education and Humanities, 2026)
The integration of local wisdom and digital technology in learning is increasingly important to support meaningful and creativity-oriented education. This study examined the need to develop an Augmented Reality (AR)-based picture storybook integrating Majalengka local wisdom for elementary school students. A qualitative descriptive approach was employed involving five teachers and ten fifth-grade students at SDN Cieurih, Majalengka. Data were collected through interviews and classroom observations and analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings revealed that teachers and students expressed the need for interactive learning materials that integrate Majalengka local wisdom, including local folktales, traditions, arts, traditional games, and environmental values. Participants perceived that AR technology could provide engaging visualizations, increase learning interest, and support activities related to idea generation, exploration, storytelling, and problem-solving. The findings also identified several implementation challenges, including limited devices, unstable internet connectivity, and teacher readiness. Overall, the findings suggest that an AR-based picture storybook may be a relevant learning medium to support students’ creative thinking and culturally contextualized learning experiences. As a preliminary needs analysis, this study did not develop or test the proposed AR-based storybook and did not measure its effectiveness in improving students’ creative thinking skills.